So you want to teach clinical? : a guide for new clinical instructors - Jaroneski, Laura A.; Przymusinski, Lori A. (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Teaching nursing students in a clinical setting with patients differs greatly from teaching in a classroom. It can be a daunting task if one is not prepared and mentored. This book provides a concise and accessible guide for nursing instructors leading students in the healthcare agency for the first time, as well as experienced educators who are interested in exploring new teaching strategies. It covers many aspects of the clinical instructor role including: meeting the nurse manager organizing and documenting your clinical day creating clinical student assignments objectively evaluating student's individual performance acknowledging diversity and inclusiveness tracking progress and handling student errors In addition, the book discusses some of the more complex issues surrounding the role of the clinical instructor such as accountability for nursing care, documentation and medication administration carried out by students. The book features numerous forms and charts to assist in organizing and managing the teaching experience, as well as situational scenarios to help prepare instructors for unique situations that arise during the clinical experience. Written by authors with extensive experience in clinical care and teaching, this book will be an invaluable guide for all clinical nursing instructors, both novice and experienced. Examples of tools in the book and online downloadable forms to support an organized clinical experience for a new instructor accompany this publication.
Before you begin -- Resources for the journey -- Role modeling and professional expectations -- Organizing and documenting your clinical day -- The development of critical thinking -- Medication administration : a complex challenge -- Alternative clinical assignments and experiences -- Diversity and inclusiveness -- Evaluation of students -- Accountability, collaboration, and professional relationships.
OCLC-licensed vendor bibliographic record.
Keywords: Clinical medicine -- Study and teaching; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; MEDICAL / Clinical Medicine; MEDICAL / Nursing / Management & Leadership